Organizational identification shaping social exchange dynamics in the workplace: an integrative approach - Tavares, S. M. (Handbook of Social Exchange Theory in Organizations, 2026)
Social exchange (SE) and organizational identification (OI) have been widely used to explain the psychological dynamics between individuals and their employing organizations, though they have largely evolved separately. Recent research has explored their combined influence. This chapter presents an integrative model of SE and OI to deepen our understanding of how individuals think, feel, and behave within organizational contexts. We propose that OI determines SE content through three mechanisms: the meaning attributed to the resource received, the value imputed to it, and the conception of role breadth among individuals with varying levels of OI. Furthermore, we examine how OI regulates SE within a two-dimensional framework, considering the hedonic value of exchange currency and the level of activity in reciprocity. We argue that OI shapes employees’ sensitivity to organization-provided exchange currencies, their expectations regarding organizational actions, their motivational drivers, and their reciprocity patterns, shaping the spectrum of behaviors used to reciprocate.